"The Way History Lands on a Face": Disability, Indigeneity, and Embodied Violence in Tommy Orange’s There There - Bushman, Brandi; Toscano, Pasquale (Disability Studies Quarterly, 2022)
At the start of Tommy Orange's There There, Cheyenne child Tony Loneman peers into his television screen and considers a playground taunt: "Why's your face look like that?" Confronted with his reflection, he discovers the "Drome"—the way fetal alcohol syndrome has contoured his body, "the way history lands on a face." The novel ends with another question from Tony: "Grandma, what are we?" With these pillared concerns—the "why" of nonnormative embodiment and the "what" of cultural identity—There There invites us to consider the ways that Indigeneity and disability are constitutive of one another. We argue that Orange (Cheyenne and Arapaho) explores how the disabled Native bodymind is always under the surveillance of the present colonial eye. We do so via close-readings of three of Tony's encounters in the novel: with himself, with an able-bodied, non-Native interlocutor who interrogates his cultural and bodymind alterity, and with his grandmother. Embodying the ancestral trauma renewed in these moments, Tony must not only live within a multi-generational temporality but must also (re)assemble his reality through constant encounters with non-Native interlocuters, moments that mimic and remind the reader of the original contact zones of American coloniality. In analyzing these moments, this article considers how disability and Indigeneity are, at once, in tension while also mutually constitutive of one another through three ongoing operations of the colonial project: the branding, transformation, and invasive reading of the bodymind. As settler colonialism continues to find its "specific, irreducible element" of territoriality not only on the geographical space of the Americas, but also on the individual bodymind, disability and Indigeneity, the corporeal and the ideological, the national and the personal, become metonymically connected and intimately imbricated.